Types of corn grown in Uzbekistan and their peculiarities (Texas Journal of Agriculture and Biological Sciences, 2022)
This article describes some species of corn of the cereal family, including varieties grown in Uzbekistan and their characteristics, ways to increase their productivity through intensive methods and their importance in agriculture